Brain and kidney GHS-R1a underexpression is associated with changes in renal function and hemodynamics during neurogenic hypertension. (1st December 2020) - Sales da Silva, Elder; Ferreira, Patrícia Maria; Castro, Carlos Henrique; Pacheco, Lilian Fernanda; Graziani, Daniel; Pontes, Carolina Nobre Ribeiro; Bessa, Amanda de Sá Martins de; Fernandes, Erika; Naves, Lara Marques; Ribeiro, Larissa Cristina dos Santos; Mendonça, Michelle Mendanha; Gomes, Rodrigo Mello; et al.
Abstract: Ghrelin is a peptide hormone whose effects are mediated by the growth hormone secretagogue receptor subtype 1a (GHS-R1a), mainly expressed in the brain but also in kidneys. The hypothesis herein raised is that GHS-R1a would be player in the renal contribution to the neurogenic hypertension pathophysiology. To investigate GHS-R1a role on renal function and hemodynamics, we used Wistar (WT) and spontaneously hypertensive rats (SHR). First, we assessed the effect of systemically injected vehicle, ghrelin, GHS-R1a antagonist PF04628935, ghrelin plus PF04628935 or GHS-R1a synthetic agonist MK-677 in WT and SHR rats housed in metabolic cages (24 h). Blood and urine samples were also analyzed. Then, we assessed the GHS-R1a contribution to the control of renal vasomotion and hemodynamics in WT and SHR. Finally, we assessed the GHS-R1a levels in brain areas, aorta, renal artery, renal cortex and medulla of WT and SHR rats using western blot. We found that ghrelin and MK-677 changed osmolarity parameters of SHR, in a GHS-R1a-dependent manner. GHS-R1a antagonism reduced the urinary Na + and K + and creatinine clearance in WT but not in SHR. Ghrelin reduced arterial pressure and increased renal artery conductance in SHR. GHS-R1a protein levels were decreased in the kidney and brain areas of SHR when compared to WT. Therefore, GHS-R1a role in the control of renal function and hemodynamics during neurogenic hypertension seem to be different, and this may be related to brain and kidney GHS-R1a downregulation. Highlights: The responses evoked from GHS-R1a on renal function and hemodynamics are altered in hypertensive rats. The changes in hemodynamic control by GHS-R1a during hypertension seems to be confined to the renal vascular bed. GHS-R1a is downregulated in SHR kidney and brain.